Laȝamon's Dialogue and English Poetic Tradition. Issue 7 (2nd October 2016) - Callander, David
ABSTRACT: This article investigates one of Laȝamon's most significant transformations of his source material, namely his greatly expanded use of dialogue. This is discussed in the context of Old English literature to examine what it might teach us about Laȝamon's literary heritage. Many different theories have been proposed for Laȝamon's connections to earlier English literature, but, in terms of dialogue, it is classical Old English poetry, particularly the saints' lives and heroic verse, which most closely resembles Laȝamon's work. The use of dialogue is one of a number of major divergences between Laȝamon and the poetry of the Anglo-Saxon Chronicle, and, in light of this, arguments linking Laȝamon to the Chronicle poems in particular are critically reviewed.